Depictions of father-daughter relationships in a selection of motion pictures - Mayet, Ahmed (My University, 2018)
A reading of the literature seems to suggest that the father-daughter relationship has not been studied to the same degree that the father-son and the mother-daughter relationship has. In the extant literature, fathers are said to be important in their children’s and daughter’s lives for several reasons (Lamb, 2000). Indeed, it is claimed that this relationship is crucial for the development of the daughter’s self-esteem (Zia, Malik, & Ali, 2015)as well as influencing her ability to relate meaningfully and deeply in relationships with men in later life (Katorski, 2003). The relative lack of research on this influential relationship is itself an incentive to examine it more extensively. Furthermore, the influence of media and that of film has also been well-established in previous research and literature, thus its depiction of father-daughter relationships would be a useful topic to research (Yazdani, 2012). Using a social constructionist framework and a previous study, this research analyzed four films depicting father- adolescent daughter relationships for the effects on the daughter’s development as a result of her father’s parenting style; this was completed using thematic analysis outlined by Braun and Clarke (2006). There was a specific criteria used for the selection of the films; the main findings posited that depictions of father-daughter relationships in these films corresponded well to research on real-life father-daughter relationships.
A research report submitted in partial fulfillment of the requirements for the degree of MA (Clinical Psychology) in the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2018.
Keywords: Fathers and daughters